ANALYSÄ°S OF THE STORY OF MR. HALÄ°L AND MRS. PERÄ°ÅžAN - SÖNMEZ , Nesim (Humanities Journal of University of Zakho, 2022)
The stories have been the subject of many researches in world literature and Kurdish literature in general. By definition, a story is a short, prose narrative that narrates a real or near-real event in a literary style. The story differs from the novel with its brevity and simple plot and few protagonists. In the story, the boundaries of the scene are generally explored, the narrator examines the subject in depth and the narration is clear.The story of Mr. Halil and Mrs. Perishan also took a literary form and became a product of Kurdish Folk Literature and folklore. Story; It passes in the Serhad region, in the region between Doğubayazid district and Subhangöl. Its main heroes are Mr. Halil, the nephew of Behlül Pasha, and Mrs. Perishan, the daughter of Omer Agha, the leader of the National Tribe. In the story, there is love on the one hand, and betrayal, absence and misery on the other. In this study, the variants of the story will be examined in terms of the narrator and its content, language, heroes, the place where the event took place and the way it happened.